Mechanics and Permeability Evolution Mechanism of Bedded Sandy Mudstone under Fluid-Solid Coupling Action - LIU Xinyu; CHAI Zhaoyun; XIN Zipeng; XIAO Chang; LIU Xiangyu; LI Tianyu; YAN Ke; DUAN Biying (Taiyuan Ligong Daxue xuebao)
[Purposes] In order to better understand the permeability changes of coal measure bedded sandy mudstone under stress, the mechanical characteristics and permeability of bedded sandy mudstone were studied by discrete element simulation on the basis of the stress seepage coupling laboratory tests. [Methods] First, the failure mode and the relationship between the full stress-strain loading process and the permeability of sandy mudstone were studied by the stress-seepage coupling laboratory tests in the bedding directions of parallel and perpendicular rock bedding. Second, in the discrete element software PFC2D, a method to characterize the flow field by solving the finite difference method is proposed for the first time, which can well reflect the stress-strain response and permeability changes of sandy mudstone, and the simulated stress-strain and permeability curves obtained are consistent with experimental results, with the fluid flowing intensively along the main fracture. Finally, according to the calibrated parameters, the stress and permeability of rock samples at different bedding angles are simulated, and the relationships between the maximum permeability or peak strength and bedding angles are explored. [Findings] The results show that the strength and permeability of layered sandy mudstone are anisotropic. The flow field direction, flow rate, and contact force chain in the rock sample are closely related to the crack, and the strong contact force chain is concentrated near the shear zone at the joint of the sample. With the increase of the bedding angle α, the peak intensity changes in a“ U” shape, and the maximum permeability decreases linearly. [Conclusions] This numerical simulation method fully takes into account the influence of rock mechanics and seepage characteristics, which provides a theoretical basis for the surrounding rock seepage prevention and reinforcement project, and a new idea for the fluid-structure interaction of discrete element simulation.